2020
DOI: 10.2174/1568009620666200720010647
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Induced Metabolism and T Cells Located in Tumor Environment

Abstract: : Several subtypes of T cells are located in a tumor environment, each of which supplies their energy using different metabolic mechanisms. Since the cancer cells require high levels of glucose, the conditions of food poverty in the tumor environment can cause inactivation of immune cells, especially the T-effector cells, due to the need for glucose in the early stages of these cells activity. Different signaling pathways such as PI3K-AKt-mTOR, MAPK, HIF-1α, etc active or inactive by the amount and type of ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 135 publications
0
1
0
Order By: Relevance
“…Various studies have found that OXPHOS and glycolysis, especially glycolytic flux, are significantly increased in effector T cells (47)(48)(49). By contrast, Tregs show a unique metabolic program that mainly utilizes mitochondrial oxidation of lipids and pyruvate (50,51).…”
Section: Contribution Of Lipid Metabolism To the Differentiation Of T Cells Into Tregsmentioning
confidence: 99%
“…Various studies have found that OXPHOS and glycolysis, especially glycolytic flux, are significantly increased in effector T cells (47)(48)(49). By contrast, Tregs show a unique metabolic program that mainly utilizes mitochondrial oxidation of lipids and pyruvate (50,51).…”
Section: Contribution Of Lipid Metabolism To the Differentiation Of T Cells Into Tregsmentioning
confidence: 99%